2015
DOI: 10.1111/tpj.12762
|View full text |Cite
|
Sign up to set email alerts
|

Leghemoglobin is nitrated in functional legume nodules in a tyrosine residue within the heme cavity by a nitrite/peroxide‐dependent mechanism

Abstract: SUMMARY Protein Tyr nitration is a post-translational modification yielding 3-nitrotyrosine (NO2-Tyr). Formation of NO2-Tyr is generally considered as a marker of nitroxidative stress and is involved in some human pathophysiological disorders, but it has been poorly studied in plants. Leghemoglobin (Lb) is an abundant hemeprotein of legume nodules that plays an essential role as O2 transporter. Liquid chromatography coupled to tandem mass spectrometry was used for a targeted search and quantification of NO2-Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…On the other hand, green pigments derived from Lbs were observed in senescing soybean nodules (Jun et al , ,b) and almost 20 years later identified as nitri‐Lbs, unveiling the generation of nitrating reactive compounds in nodules (Navascués et al , ). By contrast, Lbs bearing nitro‐Tyr are more abundant in young nodules, suggesting that they originate as a result of active nodule metabolism (Sainz et al , ). Lbs could act as scavengers of nitrogen dioxide ( .…”
Section: Globins In Symbiosismentioning
confidence: 99%
“…On the other hand, green pigments derived from Lbs were observed in senescing soybean nodules (Jun et al , ,b) and almost 20 years later identified as nitri‐Lbs, unveiling the generation of nitrating reactive compounds in nodules (Navascués et al , ). By contrast, Lbs bearing nitro‐Tyr are more abundant in young nodules, suggesting that they originate as a result of active nodule metabolism (Sainz et al , ). Lbs could act as scavengers of nitrogen dioxide ( .…”
Section: Globins In Symbiosismentioning
confidence: 99%
“…In turn, Lb levels decline significantly during nodule senescence, although the mechanisms are still poorly known. Soybean (Glycine max) Lbs can be modified by reactive nitrogen species producing in vivo derivatives bearing nitrated hemes (Navascués et al, 2012) and nitro-Tyr residues (Sainz et al, 2015). Also, Lbs undergo cross-linking and dimerization after incubation with Figure 9.…”
Section: Carbonylation Inhibits Mdh Activity and May Facilitate Lb Crmentioning
confidence: 99%
“…Indeed, leghemoglobin is metal-nitrosylated in nodules of soybean and this property was used to indirectly monitor NO levels (Sánchez et al 2010). On the other hand, recent studies revealed that leghemoglobin is also tyrosine nitrated (Sainz et al 2015). In addition, about 80 proteins have been shown recently to be S-nitrosylated in nodules of M. truncatula (Puppo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, protein tyrosine nitration appears as a prevalent post-translational modification throughout pea root development and intensifies during root senescence (Begara-Morales et al 2013). Very recently, it has been shown that leghemoglobin, an abundant hemeprotein of legume nodules, is tyrosine-nitrated in bean and soybean (Sainz et al 2015). In M. truncatula, only one protein, the glutamine synthetase (GS), has been fully characterized as a target of tyrosine nitration in nodules (Melo et al 2011).…”
mentioning
confidence: 99%